1994
DOI: 10.1111/j.1365-2710.1994.tb00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of piperacillin sodium in the presence of tazobactam sodium in 5% dextrose and normal saline injections

Abstract: The stability of piperacillin sodium in the presence of tazobactam sodium in 5% dextrose and normal saline i.v. admixtures has been determined using a modified stability-indicating high performance liquid chromatography assay method reported in the literature. The solutions were stored at room and refrigerator temperatures in plastic bags. They remained clear throughout the study although the pH values decreased slightly during storage. The solutions were stable for 2 days at 25 degrees C and for 28 days at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the latter cases, we used the MIC test strip and the SensiTitre results were confirmed. These results suggest that the majority of issues for both methods were represented by piperacillin/tazobactam, which is known to be unstable [ 31 ]. Details of AST results for each antibiotic are presented in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…In the latter cases, we used the MIC test strip and the SensiTitre results were confirmed. These results suggest that the majority of issues for both methods were represented by piperacillin/tazobactam, which is known to be unstable [ 31 ]. Details of AST results for each antibiotic are presented in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Administration by continuous or intermittent infusion was at the discretion of the treating physician. Patients treated by intermittent infusion received PIP/TAZ 4/0.5 g infused over 30 min every 6 h. Those treated by continuous infusion received a loading dose of PIP/TAZ 4/0.5 g over 30 min, followed by 4/0.5 g infused over 360 min every 6 h. Once dissolved, PIP/TAZ remains stable for 24-120 h at room temperature [12][13][14]. However, in our UCI new intravenous admixtures were prepared every 6 h. Each dose of PIP/TAZ was diluted in 100 mL of 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…As Mathew et al (1994) reported that tazobactam appeared to have a slight adverse effect on the stability of piperacillin, a stability assay of piperacillin in plasma in the presence of tazobactam was carried out. Table 5 shows the stability data corresponding to 2 months, as all the results were satisfactory and only the latest ones are presented.…”
Section: Clinical Applicationsmentioning
confidence: 99%